An inconvenient truth - Gore, Al, 1948-; Guggenheim, Davis; David, Laurie; Bender, Lawrence; Burns, Scott Z.; Skoll, Jeff.; Chilcott, Leslie; Richman, Bob.; Cassidy, Jay.; Swietlik, Dan.; Brook, Michael, 1952-; Participant Productions; et al. (Hollywood, Calif. : Paramount, 2006)
Former Vice President Al Gore explains the facts of global warming, presents arguments that the dangers of global warning have reached the level of crisis, and addresses the efforts of certain interests to discredit the anti-global warming cause. Between lecture segments, Gore discusses his personal commitment to the environment, sharing anecdotes from his experiences.
Special features: An update with former Vice-President Al Gore -- "The making of An Inconvenient truth" -- "I need to wake up" music video by Melissa Etheridge -- Commentary with director Davis Guggenheim -- Commentary with producers Laurie David, Lawrence Bender, Scott Z. Burns and Leslie Chilcott -- Free companion educational guide available at www.climatecrisis.net.
Documentary.
Released theatrically in 2006; program content: c2005.
Cinematographers, Bob Richman, Davis Guggenheim ; editors, Jay Lash Cassidy, Dan Swietlik ; music, Michael Brook.
Presenter, Al Gore.
MPAA rating: PG (for mild thematic elements).
DVD; NTSC, Region 1; widescreen; Dolby digital 5.1 surround, Dolby digital 2.0 surround.
Keywords: Gore, Al, -- 1948-; Global warming; Global warming -- Government policy -- United States; Greenhouse effect, Atmospheric; Greenhouse effect, Atmospheric -- Government policy -- United States; Environmental policy -- United States; Environmental protection -- United States; Human ecology; Risk perception; Educational films; Video recordings for hard of hearing people